2017
DOI: 10.1039/c7ta01703k
|View full text |Cite
|
Sign up to set email alerts
|

Sandwich-structured TiO2 inverse opal circulates slow photons for tremendous improvement in solar energy conversion efficiency

Abstract: To cite this version:Photon management has enabled a true revolution in the development of high-performance semiconductor materials and devices. Harnessing the highest amount of energy from photon relies on an ability to design and fashion structures to trap the light for the longer time inside the device for more electron excitation. The light harvesting efficiency in many thin-film optoelectronic devices is limited due to low photon absorbance. Here we demonstrate for the first time that slow photon circulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 60 publications
(57 reference statements)
0
24
0
Order By: Relevance
“…Furthermore, the slow photon effect and multiple scattering effect can promote the optical path, thus increasing the light absorption and further enhancing the light–matter interactions. [ 108,109 ] Therefore, PCs have good development prospects in photocatalytic fields such as photocatalytic hydrogen production, [ 110–113 ] photocatalytic degradation of pollutants, [ 114–119 ] and photocatalytic CO 2 reduction. [ 120–123 ] Table 2 shows the photocatalytic performance of some representative PCs.…”
Section: The Applications Of Pcs In Photocatalysismentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the slow photon effect and multiple scattering effect can promote the optical path, thus increasing the light absorption and further enhancing the light–matter interactions. [ 108,109 ] Therefore, PCs have good development prospects in photocatalytic fields such as photocatalytic hydrogen production, [ 110–113 ] photocatalytic degradation of pollutants, [ 114–119 ] and photocatalytic CO 2 reduction. [ 120–123 ] Table 2 shows the photocatalytic performance of some representative PCs.…”
Section: The Applications Of Pcs In Photocatalysismentioning
confidence: 99%
“…Interestingly, to further enhance PC amplification function and extend the effective optical path length of slow photon, a sandwich‐structured TiO 2 IO PCs (S‐IO‐TiO 2 ) was rationally designed. [ 118 ] The top and bottom layers of IOs have stop band peaks at about 340 nm, while the red edge of their stop band overlaps with TiO 2 electronic bandgap (≈380 nm) in [111] crystal direction. However, the middle layer IO possesses a stop band peaks at around 420 nm whose blue edge overlaps the TiO 2 bandgap ( Figure ).…”
Section: The Applications Of Pcs In Photocatalysismentioning
confidence: 99%
“…Owing to its flat configuration, FP cavity has been widely used in many areas, including lasers, [13] light-emitting diodes (LED), [42] photodetectors, [43] solar cells, [44] and photocatalysis devices. [45] In general, FP cavities are fabricated by metal, distributed Bragg reflector (DBR), and even by high-to-low refractive index interface like nanowire. In addition to conventional plano-plano FP cavity, plano-concave FP cavity also has been studied in past decade.…”
Section: Fp Cavitiesmentioning
confidence: 99%
“…[186] Figure 10b illustrated the sandwiched structure of TiO 2 inverse opal configuration, which can also be considered as a FP cavity. [45] Such sandwiched structure trapped light between the top and bottom TiO 2 layer, resulting in maximum light absorption. Compared to the monolithic counterpart, fourfold enhancement of photocurrent density and sixfold faster photocatalytic kinetics were obtained in this sandwiched structure.…”
Section: Fabry-perot Cavitymentioning
confidence: 99%
“…An immediate following question is how to introduce secondary nanostructures to further extend the light trapping of slow photons? Li and co‐workers have shown that the slow photon can be further slowed down by introducing higher order structures such as the B—R—B sandwich‐structured trilayer TiO 2 inverse opal (B refers to blue edge in resonance with TiO 2 electronic absorption edge; R refers to red edge in resonance), which resulted in an additional fivefold photocurrent density in comparison to monolithic photonic crystals. By introducing metal, the plasmonic effect has also shown intensification of light—matter interactions in addition to the photonic effect .…”
Section: Introductionmentioning
confidence: 99%